Immigrant Clusters and Homeownership in Global Metropolises: Suburbanization Trends in San Francisco, Los Angeles, and New York - Ayse Pamuk (University of California, Institute of Urban and Regional Development (IURD), 2004)
The premise of this paper is that immigrant homeownership patterns in global metropolitan housing markets are profoundly influenced by international migration dynamics and that homeownership for immigrants is realized in ethnic clusters in varying degrees and in unexpected locations of metropolitan regions. Research shows that ethnic clusters are increasingly emerging in different places and particularly in suburban areas of global metropolises as a result of some immigrants following networks of kin and friends along migration chains and bypassing inner cities altogether. In contrast to earlier theories on immigrant residential settlement patterns that view ethnic neighborhoods as disadvantaged "zones-in-transition," some of these newer clusters have unexpectedly high homeownership rates. To address the question of where immigrant homeownership is realized, 2000 Census data are used to spatially locate major immigrant groups - Chinese, Mexicans, and Filipinos - in three global metropolitan regions: San Francisco, Los Angeles, and New York. The unit of analysis is the census tract. Geographic Information Systems (GIS), a spatial analysis tool, is used to identify clusters of Chinese, Mexicans, and Filipinos. Building on past research by Logan, Alba, and Zhang (2002) on Los Angeles and New York, and Pamuk (2004) in San Francisco, an ethnic cluster is operationalized as areas with high concentrations (core) of an immigrant group and areas with a slightly lower concentration that are contiguous to it. Based on an analysis of 2000 Census data, the central finding - the suburbanization of immigrant clusters - has important policy implications for what future global metropolitan regions will look like. The dispersed suburban location of immigrant clusters and varying homeownership rates require rethinking traditional theories of residential segregation and spatial assimilation.
Keywords: 330; Suburbanisierung; Einwanderung; Wohneigentum; San Francisco <Calif.>; LosAngeles <Calif.>; New York <NY>